Radionuclide concentrations obtained from gamma-ray spectrometry for soil moisture estimation from Beech forest measurements in Lille Boegeskov, Denmark - Andreasen, Mie; Van der Veeke, Steven; Limburg, Han; Koomans, Ronald; Looms, Majken Caroline (PANGAEA, 2025)
The field site is located on clayey soil in Central Zealand, Denmark. The data is compiled into one text file and include estimated radionuclide concentrations, cosmic-ray neutron intensities, point-scale soil moisture (both time series and campaigns), as well as precipitation. Gamma radiation was measured using the gSMS100 detector (Medusa Radiometrics BV) and post-processed using the GAMMAN software (Medusa Radiometrics BV) to obtain the radionuclide concentrations (K-40, U-238, Th-232, Cs-137). The K-40, U-238, Th-232 concentrations are estimated using the Window analysis post-processing method, while the Full-Spectrum analysis post-processing method was used for Cs-137 concentrations. Cosmic-ray neutron intensities were obtained using the CR2000/B system (Hydroinnova LLC, Albuquerque, NM, USA) and were corrected for temporal changes in barometric pressure, incoming cosmic radiation, and atmospheric water vapor following standard procedures. The point-scale soil moisture time series were obtained using four stations, each consisting of five ML3 ThetaProbe sensors (Delta-T Devices). The point-scale soil moisture campaigns consist of an average of 48 measurements obtained using a handheld time domain reflectometry (TDR) sensor (Fieldscout TDR 300 Soil Moisture Meter, Spectrum Technologies, Inc.) equipped with 20 cm long rods. More details of the site characteristics, instrumentation and data processing are provided in the paper. The files contain hourly data for the period from February 8th, 2022, to January 16th, 2024.
Keywords: cosmic-ray neutrons; Gamma-ray spectrometry; tens-of-meters scale soil moisture time series